High dupilumab levels in tear fluid of atopic dermatitis patients with moderate‐to‐severe ocular surface disease. Issue 1 (16th January 2023) - Achten, Roselie; Thijs, Judith; van der Wal, Marlot; van Luijk, Chantal; van Luin, Matthijs; el Amrani, Mohsin; Knol, Edward; Delemarre, Eveline; Jager, Constance den Hartog; de Graaf, Marlies; Bakker, Daphne; de Boer, Joke; et al.
Abstract: Background: The patho‐mechanism of ocular surface disease (OSD) in dupilumab‐treated atopic dermatitis (AD) patients remains unclear. The aim of this study is to measure dupilumab levels in tear fluid and serum, and relate these findings to the severity of OSD during dupilumab treatment in AD patients. Methods: This prospective study included dupilumab‐treated moderate‐to‐severe AD patients who were seen by a dermatologist and an ophthalmologist before the start of dupilumab (baseline), and after 4 and 28 weeks of dupilumab treatment. Dupilumab levels in tear fluid and serum were measured by liquid chromatography coupled with tandem mass spectrometry (LC‐MS/MS). Additionally, a pilot study was conducted to measure dupilumab on conjunctival epithelial cells using flow cytometry and LC‐MS/MS. Results: At baseline, 89.6% ( n = 43/48) of the patients had OSD, with 50.0% having moderate‐to‐severe OSD. After 28 weeks of dupilumab treatment, the median dupilumab tear fluid levels were 0.55 mg/L (IQR 0.35–1.31) and 0.29 mg/L (IQR 0.16–0.60) in patients with moderate‐to‐severe OSD and patients with no or mild OSD, respectively ( p = 0.02). Dupilumab levels could be detected on conjunctival epithelial cells of 5 AD patients treated with dupilumab for 4 weeks. Conclusion: Patients with moderate‐to‐severe OSD had higher dupilumab tear fluid levels compared to patients with no or mild OSD, indicating that dupilumab reaches the ocular surface. Dupilumab was also detected in conjunctival cell suspensions and was found to directly bind CD45‐conjunctival epithelial cells. This suggests that AD‐induced changes of the conjunctival epithelium may play a role in the development of OSD as well as increased local drug availability.